Upaya Membangkitkan Motivasi Membaca Siswa Menggunakan Media Papan Baca di Kelas 2 SD Negeri 4 Santong Kayangan Tahun Ajaran 2023/2024 - Najia, Hulma; Mardiyanti, Nunung; Marzoan, Lalu (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2024)
This research aims to explore efforts to raise reading motivation in grade 2 students at SDN 4 Santong using reading board media. The research method used was a case study with participants in class 2 of SDN 4 Santong. Reading board media was chosen as a means to increase students' reading interest because of its ability to attract attention and visualize information in an interesting way. The research results show that the use of reading board media can be effective in increasing the reading motivation of grade 2 students, with higher levels of participation and interest in reading. The implication of this research is the need to integrate reading board media in reading learning in grade 2 elementary school in order to increase students' motivation and interest in reading.